Evaluation of customer relationship system efficiency: Applying of total cost of ownership approach - Regina Jasilionienė; Rima Tamošiūnienė (Journal of Business Economics and Management, 2009)
Calculating total cost of ownership (TCO) and benefits, building a business case and applying financial measurement methodologies help a company make right customer relationship system for investments solution and build compelling justification for its customer relationship system project. In addition, ongoing measurement of customer relationship system (CRS ) benefits ensures that an enterprise receives expected advantages and achieves strategic objectives.